Early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete, preparation method and application thereof
By using early high-strength hydrophobic anti-dissolution admixture in the initial concrete of tunnel engineering, the precipitation of calcium ions and hydroxide ions is reduced, the problem of tunnel drainage system is solved, the functionality and safety of the tunnel is improved, and carbon is realized Reduce emissions.
Patent Information
- Application Number
- CN202211720195.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-30
AI Technical Summary
Under the action of surrounding rock water, the initial concrete of tunnel engineering is prone to precipitation of calcium ions and hydroxide ions, resulting in blockage of the drainage system and affecting the functionality and safety of the tunnel. The existing anti-dissolution technology is difficult to apply to this scenario.
Using a premature high strength hydrophobic anti-dissolution admixture, including high-active admixture, hydrophobic component, premature strong component, expansion component, slump-keeping component, retarding component and fissure-limiting component, by reducing calcium ions The precipitation amount and precipitation rate with hydroxide ions can improve the permeability and strength of concrete and extend the blockage time of the drainage system.
It significantly reduces the calcium dissolution rate of the initial concrete of the tunnel, extends the service life of the drainage system, improves the functionality and safety of the tunnel, reduces maintenance costs, and achieves carbon emission reduction.
Smart Images

Figure BDA0004029484070000021 
Figure BDA0004029484070000031 
Figure BDA0004029484070000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of admixtures for tunnel engineering support concrete, and specifically relates to an early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete and a preparation method thereof, as well as application of the early high-strength hydrophobic anti-corrosion admixture in tunnel support shotcrete. Background Art
[0002] There are reports of rapid scaling and blockage of tunnel drainage pipes during operation in all countries in the world. There are more and more similar reports in my country. Dozens of tunnel drainage systems in Guangdong, Gansu, Sichuan and other provinces have been rapidly crystallized and blocked in 1 to 2 years, which has gradually attracted the attention of owners, construction units, maintenance units and scientific researchers. Existing studies have shown that: blockage of tunnel drainage pipes leads to rising groundwater levels, increasing the surrounding rock water pressure on the primary support and secondary lining concrete; surrounding rock water seeps out from the joints or cracks of the secondary lining concrete, scaling on its surface to produce white spots and affect the appearance; water seepage from the sides and arches threatens the lines, electricity and other equipment in the tunnel or causes slippery roads that affect driving; excessive surrounding rock water pressure will reduce the stability of the support structure, and the lining concrete will fall partially, directly threatening driving safety. In addition, unblocking the drainage system during operation will directly cost a lot of money: Gamisch et al. pointed out that the annual drainage system cleaning cost of a 3km long tunnel in Germany is as high as 200,000 euros; Draschitz et al. pointed out that the maintenance cost of the drainage system of a tunnel in Austria will account for 40% of the total maintenance cost during its designed 100-year service life.
[0003] At present, in the design and construction of tunnel mining methods, most of the cases at home and abroad use a composite lining of primary support and secondary lining. Among them, the primary support concrete is a temporary structure that only needs to meet the safety during construction; the secondary lining mainly bears most or all of the load and ensures the durability of the tunnel. Tunnel support concrete is constructed by shotcrete at the front end of tunnel excavation. The on-site environment is "high noise, high dust, easy to deform and collapse". The construction environment is relatively harsh and the construction progress is given priority. Therefore, the quality of the primary support concrete is difficult to guarantee. As a result, many problems mentioned above arise in the primary support concrete under the continuous action of surrounding rock water, which ultimately affect the functionality and safety of the tunnel.
[0004] Although there are many studies on the anti-corrosion of cement-based materials in existing research, such as early-strength water-resistant dispersion and anti-corrosion shield tunnel backing grouting materials, or anti-corrosion cement-based protective coatings for water-related concrete structures, these anti-corrosion technologies are not aimed at tunnel engineering support concrete and are difficult to apply to the performance improvement of primary support concrete in tunnel engineering.
[0005] Therefore, it is necessary to improve the performance of tunnel engineering support concrete to solve the problems caused by the continuous action of surrounding rock water and to improve the functionality and safety of the tunnel. Summary of the invention
[0006] The inventors of the present invention further analyzed the above phenomenon in the prior art and found that: after drying and grinding the blocking materials of the tunnel drainage pipes obtained on site, SEM and XRD were used to analyze the phase composition of the blocking materials. The results showed that the blocking materials in the mountain tunnels were almost all calcium carbonate, and the calcium carbonate and calcium sulfate contents in the blocking materials in the submarine tunnels were very high. The inventors have been tracking the tunnel construction site for a long time and conducting long-term research and found that: (1) The surrounding rock water is generally neutral or weakly alkaline, containing HCO3 - and (or) SO4 2- ions; (2) After the surrounding rock water flows through the primary support concrete (partially containing grouting materials), the pH increases and the Ca 2+ Concentrations may increase or decrease, HCO3 - Almost completely disappeared (SO4 2- The ion concentration is greatly reduced). Combining the phase changes in water quality and the thermodynamics of chemical reactions, it can be seen that the primary support concrete (partially containing grouting materials) in the tunnel project precipitates a large amount of Ca under the continuous action of surrounding rock water. 2+ With OH - ions, which increases the calcium ion concentration in the water and makes the water more alkaline (pH rises to 12 or above). 2+ With HCO3 - and (or) SO4 2- The ion reaction generates calcium carbonate and (or) calcium sulfate precipitation. In addition, alkaline water can increase the solubility of CO2 in the air in water, further generating a large amount of calcium carbonate precipitation. Calcium carbonate and (or) calcium sulfate are precipitated and scaled in the continuous drainage system (horizontal drainage pipes, longitudinal drainage pipes, side ditches and central drainage ditches, etc.), gradually blocking the drainage system, causing the water level to rise, the pressure on the primary support and secondary lining concrete to increase, the secondary lining concrete to seep or even fall, endangering driving safety, and gradually reducing the functionality and safety of the tunnel project.
[0007] Based on the universality, harmfulness and high maintenance cost of scaling and blockage in tunnel drainage systems, as well as the urgent needs of many owners, construction and maintenance units, the inventors have studied and clarified the nature of calcium dissolution of primary support concrete, which releases a large amount of calcium ions and hydroxide ions, disturbing the water body and producing a large amount of precipitation blockages. They have proposed an early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete, which can greatly reduce the precipitation amount and precipitation rate of calcium ions and hydroxide ions, and ensure the functionality and safety of the tunnel within the designed service life.
[0008] The present invention provides the following technical solutions:
[0009] An early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete comprises the following components uniformly mixed in mass fraction:
[0010]
[0011]
[0012] Among them, the high-activity admixture includes at least one of microsilica powder, microbeads and ultrafine mineral powder, and its specific surface area is generally greater than 15000m 2 / kg, 7d activity is relatively high; while the medium and low activity admixtures include at least one of fly ash, mineral powder, and limestone powder, and their specific surface area is generally around 300m 2 / kg~700m 2 / kg, the activity at 7 days is generally low.
[0013] The hydrophobic component includes at least one of polysiloxane and polysilazane.
[0014] The early strength component includes at least one of sodium sulfate, magnesium sulfate, sodium aluminate, sodium carbonate and calcium carbonate.
[0015] The expansion component includes at least one of an alumite expansion agent, a calcium sulfoaluminate expansion agent, a calcium oxide expansion agent, and an iron filings expansion agent.
[0016] The collapse-preserving component is preferably a powdered polycarboxylic acid collapse-preserving agent.
[0017] The retarding component includes at least one of glucose, sodium gluconate, phosphate and metaphosphate.
[0018] The crack-limiting component includes at least one of polypropylene (PP) fibers, polyamide (PA) fibers, polyester (PET) fibers, polyacrylonitrile (PAN) fibers and polyvinyl alcohol (PVA) fibers.
[0019] The above-mentioned early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete can be prepared by the following preparation method:
[0020] Put high-activity admixtures, medium- and low-activity admixtures, hydrophobic components, early-strength components, expansion components, collapse-preserving components, retarding components and crack-limiting components into the mixer in sequence and mix for 5 to 20 minutes until the mixture is uniform.
[0021] Another object of the present invention is to provide the application of the above-mentioned early high-strength hydrophobic and anti-corrosion admixture for tunnel engineering support concrete, that is, to add it to the tunnel support shotcrete in an amount of 5% to 30% of the cement mass fraction to replace an equal amount of cement.
[0022] Compared with common concrete such as bridge piers, box beams, and building beams, slabs, and columns, tunnel primary support concrete is sprayed rather than molded, and has more defects such as internal pores and is not dense. The primary support concrete and the invert form a ring structure, with only one side of the outside continuously bearing water pressure. Due to the special characteristics of the tunnel primary support concrete and the service environment, it generally has serious water seepage. At the same time, the cement consumption of the tunnel primary support concrete is relatively high (400kg / m 3 ~600kg / m 3 ), the hydration products contain a lot of calcium ions and hydroxide ions, and it is very easy for calcification precipitation to block the drainage system. The present invention aims to give full play to the synergistic effect of "low calcium, solid calcium, increased density, impermeability, and easy construction" among the components on the basis of the inventor's clarification of its damage mechanism, significantly improve the corrosion resistance of the primary support concrete of the tunnel project, greatly extend the scaling and clogging time of the tunnel drainage system, ensure the functionality and safety of the tunnel within the designed service life, and reduce maintenance costs. Its mechanism of action is briefly described as follows:
[0023] High-activity admixtures and medium-low-activity admixtures exert their high early reactivity and secondary volcanic ash effect in the later stage, reducing the total amount of soluble calcium ions and hydroxides in hardened concrete, playing a "low-calcium effect". Hydrophobic components such as polysiloxane or polysilazane can reduce the transmission rate of water in the primary concrete matrix, and further reduce the dissolution rate of calcium ions or hydroxide ions carried by water, playing a "calcium-fixing effect". Since the amount of cement in shotcrete is relatively high, the addition of fiber-based crack-limiting components can effectively prevent the cracking of hardened concrete, reduce the seepage points of primary concrete, and play an "anti-seepage effect". Early strength components can further activate the activity of high, medium and low-activity admixtures, reduce the rebound of shotcrete, and play an "easy construction effect". Since shotcrete is sprayed onto the surrounding rock surface with pulsed high-pressure air, there are often some bubbles in the primary concrete, and the matrix density is often not high. Adding expansion components such as calcium sulfoaluminate expansion agent or calcium oxide expansion agent can increase the density of the primary concrete in the later stage, improve its own impermeability, and play a "densification effect". The collapse-preserving component and the retarding component can ensure that the concrete has good workability before spraying, and also play a "easy construction effect".
[0024] The advantages and beneficial effects of the present invention are as follows:
[0025] 1. The early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete provided by the present invention also contains an appropriate amount of collapse-preserving component and retarding component, which can effectively ensure the workability of premixed concrete during wet spraying process, the early strength component effectively reduces the rebound of shotcrete, the high, medium and low activity admixtures reduce the total amount of soluble calcium ions and hydroxides in the primary support concrete, the crack-limiting component reduces the number of leakage points of the support concrete after hardening, the expansion component improves the matrix impermeability in the middle and late stages, and the hydrophobic component effectively reduces the dissolution rate of calcium ions or hydroxide ions carried by water. The above multiple components work together to improve the overall strength and impermeability of the primary support concrete, and significantly reduce the calcium dissolution rate of the matrix, so as to significantly inhibit the reduction of the dissolution strength of the primary support concrete, and at the same time extend the blocking time of the drainage system to ensure the long-term safe service of the tunnel structure.
[0026] 2. The early high-strength hydrophobic and anti-corrosion admixture for tunnel engineering support concrete provided by the present invention is added to the tunnel support shotcrete at a dosage of 5% to 30% of the mass fraction of cement, replacing an equal amount of cement. It is easy to use and does not require additional processes.
[0027] 3. The present invention can save up to 30% of cement usage in primary support concrete. However, the cement production process emits a large amount of carbon dioxide, causing many environmental problems. Therefore, the use of early high-strength hydrophobic and anti-corrosion admixtures in tunnel engineering support concrete helps achieve the goal of carbon emission reduction. DETAILED DESCRIPTION
[0028] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0029] Preparation Example 1
[0030] 37% microsilica powder, 25% fly ash, 18% polysiloxane, 5% sodium sulfate, 1% magnesium sulfate, 4% calcium oxide, 4% magnesium oxide, 2% powdered polycarboxylic acid collapse preventer, 2% sodium gluconate and 2% polypropylene fiber are put into a mixer in sequence according to mass fraction and mixed for 20 minutes until uniform to obtain the early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete.
[0031] Preparation Example 2
[0032] 37% microsilica powder, 25% mineral powder, 18% polysiloxane, 5% sodium sulfate, 1% magnesium sulfate, 4% calcium oxide, 4% magnesium oxide, 2% powdered polycarboxylic acid collapse preventer, 2% sodium gluconate and 2% polypropylene fiber are put into a mixer in sequence according to mass fraction and mixed for 20 minutes until uniform to obtain the early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete.
[0033] Preparation Example 3
[0034] 38% microsilica powder, 26% fly ash, 10% polysilazane, 10% sodium aluminate, 10% calcium sulfoaluminate expansion agent, 2% powdered polycarboxylic acid collapse preventer, 2% sodium gluconate and 2% polyamide fiber are put into a mixer in sequence according to mass fraction and mixed for 20 minutes until uniform to obtain the early high-strength hydrophobic and anti-corrosion admixture for tunnel engineering support concrete.
[0035] Preparation Example 4
[0036] 33% microsilica powder, 23% limestone powder, 16% polysilazane, 10% sodium aluminate, 10% calcium oxide expansion agent, 3% powdered polycarboxylic acid collapse preventer, 3% sodium gluconate and 2% polyamide fiber are put into a mixer in sequence according to mass fraction and mixed for 20 minutes until uniform to obtain the early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete.
[0037] Preparation Example 5
[0038] 38% ultrafine mineral powder, 20% fly ash, 16% polysiloxane, 10% sodium sulfate, 10% alum stone expansion agent, 2% powdered polycarboxylic acid collapse preventer, 2% glucose and 2% polyacrylonitrile are sequentially added into a mixer according to mass fraction and mixed for 20 minutes until uniform to obtain the early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete.
[0039] In order to demonstrate the necessity of the components in the early high-strength hydrophobic anti-corrosion admixture provided by the present invention, the following comparative experiment was conducted.
[0040] Preparation Comparative Example 1
[0041] In this comparative preparation example, the same points as those in the above-mentioned preparation example 1 are not described here, and only the differences therefrom are described. The difference between this comparative preparation example and preparation example 1 is that the hydrophobic component polysiloxane is not used, and an equal amount of fly ash is used instead; the rest is referred to as described in preparation example 1 to obtain a first comparative admixture.
[0042] Preparation Comparative Example 2
[0043] In this comparative preparation example, the same points as those in the above-mentioned preparation example 1 are not described here, and only the differences therefrom are described. The difference between this comparative preparation example and preparation example 1 is that the early strength components sodium sulfate and magnesium sulfate are not used, and are replaced by an equal amount of fly ash; the rest is referred to as described in preparation example 1 to obtain a second comparative admixture.
[0044] Preparation Comparative Example 3
[0045] In this comparative preparation example, the same points as those in the above-mentioned preparation example 1 are not described here, and only the differences therefrom are described. The difference between this comparative preparation example and the preparation example 1 is that the collapse retaining component powdered polycarboxylic acid collapse retaining agent and the retarding component sodium gluconate are not used, and an equal amount of fly ash is used instead; the rest is referred to the preparation example 1 to obtain a third comparative admixture.
[0046] In order to verify the application performance of the early high-strength deep sleep anti-corrosion admixtures provided by the above-mentioned preparation examples and the comparative admixtures provided by the preparation comparison examples, the following multiple application examples and application comparison examples are provided.
[0047] Application Example 1
[0048] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 1 was added to the tunnel support shotcrete at a dosage of 5% of the mass fraction of cement, replacing an equal amount of cement.
[0049] Application Example 2
[0050] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 1 was added to the tunnel support shotcrete at a dosage of 10% of the mass fraction of cement, replacing an equal amount of cement.
[0051] Application Example 3
[0052] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 1 was added to the tunnel support shotcrete at a dosage of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0053] Application Example 4
[0054] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 1 was added to the tunnel support shotcrete at a dosage of 30% of the mass fraction of cement, replacing an equal amount of cement.
[0055] Application Example 5
[0056] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 2 was added to the tunnel support shotcrete at a dosage of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0057] Application Example 6
[0058] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 3 was added to the tunnel support shotcrete at a dosage of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0059] Application Example 7
[0060] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 4 was added to the tunnel support shotcrete at a dosage of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0061] Application Example 8
[0062] The early high-strength hydrophobic anti-corrosion admixture provided in the above-mentioned Preparation Example 5 was added to the tunnel support shotcrete at a dosage of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0063] Application Comparative Example 1
[0064] The first comparative admixture provided in the above-mentioned preparation comparative example 1 was added to the tunnel support shotcrete in an amount of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0065] Application Comparative Example 2
[0066] The second comparative admixture provided in the above-mentioned preparation comparative example 2 was added to the tunnel support shotcrete at a dosage of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0067] Application Comparative Example 3
[0068] The third comparative admixture provided in the above-mentioned preparation comparative example 3 was added to the tunnel support shotcrete at an amount of 20% of the mass fraction of cement, replacing an equal amount of cement.
[0069] A large concrete slab was sprayed using a wet spraying machine according to the blank group (i.e., without any anti-corrosion admixtures) in Table 1, the tunnel support shotcrete provided in each application embodiment and the application comparison example. After 24 hours, the test blocks of different sizes were cut to obtain test blocks, which were cured to different ages and tested for various performance indicators. The specific operation process and test indicators are as follows: (1) Fresh concrete was obtained by stirring according to the proportion in Table 1 (without accelerating setting agent), and the initial slump was tested. After standing for 1.5 hours, it was stirred again for 20 seconds, and its slump was tested again; (2) The first step of fresh concrete and the alkali-free accelerating setting agent shown in Table 1 were sprayed using a wet spraying machine to obtain a large concrete slab. Nine 100mm×100mm×100mm cubic test blocks (divided into groups of three for subsequent testing) and three Φ50mm×100mm cylindrical test blocks were obtained by cutting and drilling. The three cubic test blocks were tested for 1d compressive strength and the three cubic test blocks were tested for 28d compressive strength. (3) After 28 days of standard curing, the last three cubic specimens were immersed in 6 mol / L NH4Cl solution to obtain the calcium ion dissolution rate after immersion for 30 days. The NH4Cl solution was replaced every 7 days. The calcium ion concentration in the immersion solution was tested by ICP plasma spectrometry. The cumulative calcium ion dissolution after immersion for 30 days was calculated by combining the solution volume and superposition method. The initial total calcium content in the specimen was calculated based on the calcium content in the compound and cementitious materials, and finally the calcium ion dissolution rate after 30 days was calculated. After 30 days of dissolution, the compressive strength of the cubes was tested.
[0070] Table 1 Mix ratio of shotcrete for tunnel support using wet shotcrete technology (kg / m 3 )
[0071]
[0072] The workability and hardened concrete performance test results of the tunnel support shotcrete of the blank group, various application examples and application comparison examples shown in Table 1 are shown in Table 2.
[0073] Table 2 Test results of tunnel support shotcrete workability and hardened concrete performance
[0074]
[0075] It can be seen from Table 2 that: (1) The early high-strength hydrophobic anti-corrosion admixtures prepared in Examples 1 to 8 contain appropriate amounts of slump-retaining components and retarding components, and the slump at 1.5h is between 170mm and 200mm, which can effectively ensure the workability of premixed concrete during the wet spraying process; (2) The presence of early strength components and highly active mineral admixtures significantly improves the strength at 1d and 28d, and the 28d compressive strength is 1 to 2 strength grades higher (5MPa to 10MPa), and the permeability at 28d is (3) Due to the secondary volcanic ash effect of the hydrophobic component and the admixture, the calcium ion dissolution rate after immersion in 6 mol / L NH4Cl solution for 30 days is greatly reduced by 60% to 96%, which will significantly reduce the precipitation production; (4) The calcium dissolution rate in the blank group is 30.3%, and the corresponding residual strength is reduced by 68%, while the calcium dissolution rate in the application example 3 is 1.1%, and the residual strength is reduced by nearly 2.5%, so the strength of the tunnel engineering support concrete after dissolution is better guaranteed.
[0076] Further comparison shows that: (1) The composition of the early high-strength hydrophobic anti-corrosion admixtures used in Application Examples 1 to 4 is consistent. With the increase of the dosage, the 28d compressive strength gradually increases. The effect is best when the dosage is 20%, and the effect is not further improved when the dosage is 30%. The rules of impermeability, calcium ion dissolution rate and dissolution strength guarantee rate are consistent; (2) Compared with Application Example 3, the main difference in the composition of the early high-strength hydrophobic anti-corrosion admixture used in Application Example 5 is that the low-activity admixture in the former is fly ash, and the low-activity admixture in the latter is slag powder. The 1d and 28d compressive strength indicators of Application Example 5 are better than those of Application Example 3, and the 30d compressive strength indicators are better than those of Application Example 3. The performance after accelerated dissolution is slightly worse than that of Application Example 3, but much better than that of the blank group; (3) Compared with Application Example 3, Application Examples 6 to 8 also adjusted the types or dosages of high-activity admixtures, medium- and low-activity admixtures, hydrophobic components, early strength components, expansion components, collapse-retaining components, retarding components or crack-limiting components, and the 1d, 28d compressive strength indicators and the performance after 30d accelerated dissolution changed slightly, but much better than that of the blank group; (4) Compared with Application Example 3, Application Comparative Examples 1 to 3 lacked hydrophobic components, early strength components and collapse-retaining and retarding components, respectively, and as a result, the 1d, 28d compressive strength indicators and the performance after 30d accelerated dissolution showed large fluctuations.
[0077] From the above analysis, it can be seen that the effect of the early high-strength hydrophobic anti-corrosion admixture provided by the present invention is produced by the synergistic effect of each component: the collapse-preserving component and the retarding component can effectively ensure the workability of the premixed concrete during the wet spraying process, focusing on the "easy construction effect"; the early strength component effectively reduces the rebound amount of the shotcrete, focusing on the "easy construction effect"; the high-activity admixture and the medium- and low-activity admixture reduce the total amount of soluble calcium ions and hydroxides in the primary support concrete, focusing on the "low calcium effect"; the crack-limiting component reduces the number of leakage points of the supporting concrete after hardening, focusing on the "anti-seepage effect"; the expansion component improves the matrix anti-seepage in the middle and late stages, focusing on the "densification effect"; the hydrophobic component effectively reduces the dissolution rate of calcium ions or hydroxide ions with water as the carrier, focusing on the "calcium-fixing effect". The above components work together to improve the overall strength and impermeability of tunnel engineering support concrete, and significantly reduce the calcium dissolution rate of the matrix, which significantly inhibits the reduction of support concrete dissolution strength, while extending the blocking time of the drainage system and ensuring the long-term safe service of the tunnel structure. If any component is missing, it will affect the construction performance or the effect of improving anti-dissolution performance.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An early high-strength hydrophobic anti-corrosion admixture for tunnel engineering support concrete, characterized in that: It is composed of the following components mixed evenly by mass fraction: The high-activity admixture is selected from at least one of microsilica powder, microbeads and ultrafine mineral powder, and its specific surface area is greater than 15000m 2 / kg; the medium and low activity admixture is selected from at least one of fly ash, mineral powder and limestone powder, and its specific surface area is 300m 2 / kg~700m 2 / kg; The hydrophobic component is selected from at least one of polysiloxane and polysilazane.
2. The early high-strength hydrophobic anti-corrosion admixture according to claim 1, characterized in that: The early strength component is selected from at least one of sodium sulfate, magnesium sulfate, sodium aluminate, sodium carbonate and calcium carbonate.
3. The early high-strength hydrophobic anti-corrosion admixture according to claim 1, characterized in that: The expansion component is selected from at least one of alumite expansion agent, calcium sulfoaluminate expansion agent, calcium oxide expansion agent and iron filings expansion agent.
4. The early high-strength hydrophobic anti-corrosion admixture according to claim 1, characterized in that: The collapse-preserving component is a powdered polycarboxylic acid collapse-preserving agent.
5. The early high-strength hydrophobic anti-corrosion admixture according to claim 1, characterized in that: The retarding component is selected from at least one of glucose, sodium gluconate, phosphate and metaphosphate.
6. The early high-strength hydrophobic anti-corrosion admixture according to claim 1, characterized in that: The crack-limiting component is selected from at least one of polypropylene fibers, polyamide fibers, polyester fibers, polyacrylonitrile fibers and polyvinyl alcohol fibers.
7. The method for preparing the early high-strength hydrophobic anti-corrosion admixture according to any one of claims 1 to 6, characterized in that: Includes steps: Put high-activity admixtures, medium- and low-activity admixtures, hydrophobic components, early-strength components, expansion components, collapse-preserving components, retarding components and crack-limiting components into the mixer in sequence and mix for 5 to 20 minutes until the mixture is uniform.
8. The use of the early high strength hydrophobic anti-corrosion admixture as claimed in any one of claims 1 to 6, characterized in that: The early high-strength hydrophobic anti-corrosion admixture is added to the tunnel support shotcrete in an amount of 5% to 30% of the cement mass fraction, and replaces an equal amount of cement.
Citation Information
Patent Citations
Multi-component composite synergist for shotcrete and preparation method of multi-component composite synergist
CN111574103A
Tunnel lining concrete anti-corrosion admixture as well as preparation method and application thereof
CN113845329A
Cited By
Calcium corrosion resistant sprayed concrete and preparation method thereof
CN121135316A
